Critical Media Literacy With and Within Generative AI: Desing Based Research on #PinchaLaBurbuja platform - Pedroche-Santovena, Itziar; Feliz-Murias, Tiberio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article presents the design phase of the platform #PinchaLaBurbuja, an environment aimed at fostering critical media literacy through the use of generative artificial intelligence, with the goal of promoting critical agency in postdigital contexts. The proposal introduces three key innovations: GPT-based cyborgs developed using agent prompting techniques and RAG architecture, grounded in the principles of affective polarization, post-truth, and virality; a critical reformulation of inoculation theory; and the discursive evaluation of AI as an educational actor. Employing a Design-Based Research (DBR) approach, the study analyzes emerging patterns, the application of critical inoculation, and the pedagogical self-awareness of the cyborgs. The results reveal epistemic contrast patterns, bias reduction, and argumentative refutation, alongside areas for improvement in gamification and traceability.